Play Therapy and Youth Experiencing Homelessness - Rachel Wiskind (Columbia Social Work Review, 2018)
Youth experiencing homelessness suffer both short-term and long- term negative effects: the rate of mental health problems in the United States (U.S.) seems to be higher for youth experiencing homelessness than for the general population (Baggerly, 2004), and twenty percent of adults experiencing homelessness were homeless as children (National Coalition for the Homeless, 1999). Child-centered play therapy (CCPT) has been shown to offer positive short-term effects on self-esteem, developmental delays, and other socio-emotional delays of U.S. youth (Leblanc & Ritchie, 2001). While CCPT shows promise, the benefits of CCPT for youth experiencing homelessness are underexplored. It is imperative that social workers study the potential longitudinal benefits of CCPT specifically for youth experiencing homelessness so that they can continue to provide the most effective therapies to their clients in the short and long terms.